MMP-2 and TIMP-2 in the prostates of male and female mongolian gerbils: Effects of hormonal manipulation - Rochel-Maia, Sabrina S.; Santos, Fernanda C. A. [UNESP]; Vilamaior, Patrícia S. L. [UNESP]; Justulin Jr., Luis A.; Felisbino, Sérgio L. [UNESP]; Góes, Rejane M. [UNESP]; Taboga, Sebastião R. [UNESP] (My University, 2011)
TIMPs in the prostates of male and female gerbils and evaluated the effects of testosterone on the expression of these enzymes. Ventral prostates from male gerbils that were either intact or had been castrated for 7 or 21 days, along with prostates from female gerbils that were either intact or had been treated with testosterone for 7 or 21 days, were submitted to histological, stereological and immunohistochemical analyses. Stereology of prostatic components showed significant alterations of tissue compartments in the ventral male prostate after castration, especially after 21 days, with a significant increase in stroma. Administration of testosterone led to disorganization in the female prostate, with a significant increase in collagen fibers and smooth muscle cells after 21 days, along with the development of epithelial lesions such as PINs. MMP-2 increased after 21 days of castration in males; however, the TIMP-2 immunoreaction for this group was weak or absent. In females, the expression of MMP-2 appeared to decrease after 7 days of treatment with testosterone, but after 21 days, both epithelium and stroma showed a stronger reaction for MMP-2 than the controls. The expression of TIMP-2 in the treated females was similar to its expression in the castrated males. We conclude that the distribution of MMPs and TIMPs in both male and female prostates is altered by androgen manipulation, but the mechanism of stromal regulation appears to be distinct between genders because both the lack of T in castrated males and the excess levels of T in treated females lead to the same effect.
Keywords: Female prostate; MMP; Testosterone; TIMP; Ventral prostate; androgen; gelatinase A; testosterone; tissue inhibitor of metalloproteinase 2; animal; drug effect; enzymology; female; gerbil; immunohistochemistry; male; metabolism; orchiectomy; prostate; sexual development; Androgens; Animals; Female; Gerbillinae; Immunohistochemistry; Male; Matrix Metalloproteinase 2; Orchiectomy; Prostate; Sex Characteristics; Tissue Inhibitor of Metalloproteinase-2; Meriones unguiculatus